2021
DOI: 10.1167/tvst.10.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nuclear Gene Expression Related to Mitochondrial Function Affect Extracellular Matrix, Collagens, and Focal Adhesion in Keratoconus

Abstract: Purpose Mitochondrial DNA (mtDNA) abnormalities were previously found to be causative in the pathogenesis of various diseases. Here, comprehensive mitochondrial and nuclear sequence and transcript analyses, along with analyses of the methylation aspects of nuclear genes related to mitochondrial function, were performed in patients with keratoconus (KTCN) to evaluate their contribution to the KTCN pathogenesis. Methods Blood mtDNA of 42 KTCN and 51 non-KTCN individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Also, GO terms enrichment analysis indicated mainly molecular processes associated with the regulation of transcription processes and DNA binding were revealed in the GO assessment. This is in line with our previous studies on KTCN corneas as we had identified differentially expressed genes that were involved in ECM organization, and signal transduction, including Wnt signaling pathways, disrupted in KTCN, assessing transcriptomic (Kabza et al, 2017b;Karolak et al, 2020b), genomic (Karolak et al, 2020a), and mitochondrial features (Nowak-Malczewska et al, 2021). Moreover, in our continuous study on additional corneal samples derived again from unrelated Polish patients with KTCN, we have identified both coding and noncoding sequence variation in genes that are involved, among others, in ECM and Wnt signaling (Jaskiewicz et al, 2023a).…”
Section: Discussionsupporting
confidence: 89%
“…Also, GO terms enrichment analysis indicated mainly molecular processes associated with the regulation of transcription processes and DNA binding were revealed in the GO assessment. This is in line with our previous studies on KTCN corneas as we had identified differentially expressed genes that were involved in ECM organization, and signal transduction, including Wnt signaling pathways, disrupted in KTCN, assessing transcriptomic (Kabza et al, 2017b;Karolak et al, 2020b), genomic (Karolak et al, 2020a), and mitochondrial features (Nowak-Malczewska et al, 2021). Moreover, in our continuous study on additional corneal samples derived again from unrelated Polish patients with KTCN, we have identified both coding and noncoding sequence variation in genes that are involved, among others, in ECM and Wnt signaling (Jaskiewicz et al, 2023a).…”
Section: Discussionsupporting
confidence: 89%
“…No differences were found in the mtDNA methylation sequencing, suggesting that the role of mtDNA methylation modifications in KTCN was not responsible for expression differences. The deeper mechanisms are worth exploring [ 202 ].…”
Section: Methylation In Cdsmentioning
confidence: 99%